RECONSTRUCTION OF THE REGULATION GOVERNING AD HOC JUDGES IN THE INDUSTRIAL RELATIONS COURT OF INDONESIA - Pamungkas, Yogo; Amriyati, Amriyati; Yurikosari, Andari; Setiawati, Anda; Lie, Ribka Yonathan (Kanun Jurnal Ilmu Hukum, 2024)
This article examines the current construction of ad hoc judges within the Industrial Relations Court (PHI) and the resulting challenges impacting the settlement of industrial relations disputes. The primary objective of this analysis is to identify the legal problems associated with the present framework regulating ad hoc PHI judges and to propose solutions that mitigate these weaknesses. Utilizing a normative qualitative research methodology, this study relies on secondary data, employing both a statutory and conceptual approach to comprehension. Findings suggest that the existing construction of ad hoc PHI judges may compromise the objectivity of their decisions. This potential for bias can adversely affect fair conflict resolution, undermining trust in the judicial process. In light of these findings, the article advocates for a comprehensive reconstruction of the regulatory framework governing ad hoc judges. This would involve legislative reforms aimed at enhancing the performance and quality of PHI ad hoc judges. Such reforms could include stricter selection criteria, ongoing training programs, and mechanisms for accountability to ensure that these judges can make impartial and informed decisions. Ultimately, by addressing the identified legal shortcomings and implementing the proposed solutions, the integrity of the industrial relations dispute resolution process can be significantly improved. This approach not only aims to safeguard justice and fairness in industrial relations but also enhances the overall efficacy of the legal system in Indonesia. The insights underscore the urgent need for legislative action to foster a robust and unbiased framework for ad hoc PHI judges, ensuring equitable outcomes for all parties involved in industrial disputes.